An Efficient Method for the Isolation and Cultivation of Hypothalamic Neural Stem/Progenitor Cells From Mouse Embryos - Yichao Ou; Yichao Ou; Mengjie Che; Junjie Peng; Mingfeng Zhou; Guangsen Wu; Haodong Gong; Haodong Gong; Kai Li; Xingqin Wang; Peirong Niu; Songtao Qi; et al. (Frontiers Media S.A., 2022)
The hypothalamus is the key region that regulates the neuroendocrine system as well as instinct behaviors, and hypothalamic dysfunction causes refractory clinical problems. Recent studies have indicated that neural stem/progenitor cell (NSPC) in the hypothalamus play a crucial role in hypothalamic function. However, specific hypothalamic NSPC culture methods have not been established, especially not detailed or efficient surgical procedures. The present study presented a convenient, detailed and efficient method for the isolation and cultivation of hypothalamic NSPCs from embryonic day 12.5 mice. The procedure includes embryo acquisition, brain microdissection to quickly obtain hypothalamic tissue and hypothalamic NSPC culture. Hypothalamic NSPCs can be quickly harvested and grow well in both neurosphere and adherent cultures through this method. Additionally, we confirmed the cell origin and evaluated the proliferation and differentiation properties of cultured cells. In conclusion, we present a convenient and practical method for the isolation and cultivation of hypothalamic NSPCs that can be used in extensive hypothalamic studies.